Science - Art - van Berkum, Ans; Blekkenhorst, Tom; van der Blij, Frederik; Swan Liat, Kwee; van der Wolk, Johannes; Reffin Smith, Brian (Utrecht : Fentener van Vlissingen Fund)
This book is about the search for innovative combinations of art, science and technology.
Engels
boek